Heritable base-editing in Arabidopsis using RNA viral vectors - Degao Liu; Shuya Xuan; Lynn E Prichard; Lilee I Donahue; Changtian Pan; Ugrappa Nagalakshmi; Evan E. Ellison; Colby G. Starker; Savithramma P. Dinesh‐Kumar; Yiping Qi; Daniel F. Voytas (2022)
Heritable base-editing using a viral delivery system enables high-throughput functional analysis of genes in Arabidopsis.